2016
DOI: 10.1186/s12916-016-0688-1
|View full text |Cite
|
Sign up to set email alerts
|

Current state of ethics literature synthesis: a systematic review of reviews

Abstract: BackgroundModern standards for evidence-based decision making in clinical care and public health still rely solely on eminence-based input when it comes to normative ethical considerations. Manuals for clinical guideline development or health technology assessment (HTA) do not explain how to search, analyze, and synthesize relevant normative information in a systematic and transparent manner. In the scientific literature, however, systematic or semi-systematic reviews of ethics literature already exist, and sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
91
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(91 citation statements)
references
References 42 publications
0
91
0
Order By: Relevance
“…25 There are different types of SRs of argumentative literature, for example, SRs of (ethical) issues, conclusions, concepts, recommendations and reasons. 28 Even if SRs are a rather new methodological approach within the field of bioethics, there have been comprehensive publications on the value of such reviews, 29,30 and several SRs of argumentative literature in general 31 and specifically of SRs of reasons have been already conducted and published. [32][33][34]…”
Section: Methodsmentioning
confidence: 99%
“…25 There are different types of SRs of argumentative literature, for example, SRs of (ethical) issues, conclusions, concepts, recommendations and reasons. 28 Even if SRs are a rather new methodological approach within the field of bioethics, there have been comprehensive publications on the value of such reviews, 29,30 and several SRs of argumentative literature in general 31 and specifically of SRs of reasons have been already conducted and published. [32][33][34]…”
Section: Methodsmentioning
confidence: 99%
“…Thus, in a certain way, this study is a further follow-up of earlier publications where we presented the results of systematic reviews of normative literature, which is why the structure was kept approximatively the same. 4,8 Research design…”
Section: Objectivementioning
confidence: 99%
“…Regarding systematic reviews of normative literature, our earlier publications reported some methodological shortcomings. 4,8 In order to adapt such a methodology, it is essential to first gain an overview of the standards currently used in systematic reviews of bioethical literature, including the empirical one which has not been investigated yet.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, using a systematic literature review to answer a research question in philosophical ethics is not entirely new. [34,35] Mertz et al [36] note that systematic reviews of ethics literature exist (for example, Parris and Peachey [33] used systematic reviews to empirically examine how the construct 'servant leadership' is morally defined in published ethical literature, and applied to organisational settings) and also encourage such use -specifically for contributing normative inputs for evidencebased ethical decision-making in clinical care. Decision-making within the clinical context, they contend, is strongly based on external knowledge, such as knowledge of moral philosophy and applied ethics.…”
mentioning
confidence: 99%
“…Non-systematic reviews could also diminish the quality and application of such external knowledge to ethical decision-making. Pae [37] and others [35,36] add that literature reviews such as narrative reviews and eminence-based reviews, which fail to include pre-specified eligibility criteria, can result in methodological shortcomings, leading to bias that may influence an author's interpretation and/or conclusions, 37] or reducing methodological transparency regardless of the actual methodological quality of a study.…”
mentioning
confidence: 99%